2014
DOI: 10.1080/02188791.2014.963506
|View full text |Cite
|
Sign up to set email alerts
|

Corruption risks of private tutoring: case of Georgia

Abstract: The paper focuses on teacher-supplied private tutoring in the context of post-Soviet Georgia, and elucidates the ways in which teacher-supplied private tutoring can be related to educational corruption. The paper draws on data from in-depth interviews of 18 school teachers in different parts of Georgia in 2013. The findings of the qualitative study indicate challenges that teachers face as a result of their dual lives between schools and private tutoring. The challenges include moral dilemmas related to tutori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 13 publications
1
28
1
4
Order By: Relevance
“…However, patterns may be complex when teachers also provide private lessons: students who are satisfied with their teachers may have higher possibility to receive private tutoring from those teachers. Further, teacher's corruption, such as intentionally teaching less during school hours (Jayachandran 2014) or deliberately deflating students' marks (Kobakhidze 2014), may coerce students to seek tutoring whether or not they are satisfied with their teachers.…”
Section: Literature On Determinants Of Demand For Tutoringmentioning
confidence: 99%
“…However, patterns may be complex when teachers also provide private lessons: students who are satisfied with their teachers may have higher possibility to receive private tutoring from those teachers. Further, teacher's corruption, such as intentionally teaching less during school hours (Jayachandran 2014) or deliberately deflating students' marks (Kobakhidze 2014), may coerce students to seek tutoring whether or not they are satisfied with their teachers.…”
Section: Literature On Determinants Of Demand For Tutoringmentioning
confidence: 99%
“…Some of the teachers deliberately provide substandard knowledge and guidance in the classroom, and do not teach the whole syllabus to ensure that the students come to get extra classes from them (Aslam, 2011;Silova et al, 2006). It is also reported that some teachers give undue favors to those students who take shadow education from them, and also force the parents to send their children to them for extra coaching (Kobakhidze, 2014). Shadow education also affects the financial situation of the families especially those form middle and lower classes as it consumes a large chunk of family income and increases the gap between higher and lower classes (Aslam, 2011;Bray, 2009;De, Barik, Samanta, Bhattacharya, Biswas, Dasgupta, & Raychaudhuri, 2009).…”
Section: Disadvantages Of Shadow Educationmentioning
confidence: 99%
“…Further when teachers are also tutors they may reserve their energies for the private lessons, knowing that they will receive their standard salaries provided their school-based work is not seriously problematic (see e.g. Bray et al 2016;Kobakhidze 2014;Hartmann 2013). These situations arise in almost all countries, including China, and create a need for what Kodakos and Kalavasis (2015) have called "border management models".…”
Section: Global Patterns and Implications Of Shadow Educationmentioning
confidence: 99%